1992
DOI: 10.1159/000200917
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate Acid Suppression for the Management of Gastro-Oesophageal Reflux Disease

Abstract: Gastro-oesophageal reflux disease (GORD) results from an abnormally prolonged dwell time of acidic gastric contents in the oesophagus. Although GORD is primarily a motor disorder, the injurious effects of gastric acid are central to the pathogenic process of oesophagitis, and the severity of disease correlates with the degree and duration of oesophageal acid exposure. In the majority of patients with mild disease, oesophageal acid exposure occurs predominantly during post-prandial periods. Conventional doses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
423
2
11

Year Published

1995
1995
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 489 publications
(447 citation statements)
references
References 20 publications
11
423
2
11
Order By: Relevance
“…In human, maintenance of a pH above 3 and 4 for a minimum of 16 hours is required for healing of gastric ulceration and reflux esophagitis, respectively 78. Initial studies suggested that once daily administration of omeprazole results in 24 hours of acid suppression,79, 80 however, the duration of acid suppression after PO dosing at 4 mg/kg might be as short as 12 hours in some animals 66.…”
Section: Treatment and Preventionmentioning
confidence: 99%
“…In human, maintenance of a pH above 3 and 4 for a minimum of 16 hours is required for healing of gastric ulceration and reflux esophagitis, respectively 78. Initial studies suggested that once daily administration of omeprazole results in 24 hours of acid suppression,79, 80 however, the duration of acid suppression after PO dosing at 4 mg/kg might be as short as 12 hours in some animals 66.…”
Section: Treatment and Preventionmentioning
confidence: 99%
“…In this condition, the clinical effect of treatment is clearly proportional to the degree and duration of acid suppression. 47 The effect of histamine H 2 -receptor antagonists in long-term treatment of GERD has generally been disappointing, at least in patients with high-grade oesophagitis. 48 This has led to a widespread use of proton pump inhibitors in the treatment of GERD, and the long duration of effect of the proton pump inhibitors has led to the use of these drugs even in patients with low-grade in¯ammation.…”
Section: Clinical Consequencesmentioning
confidence: 99%
“…It is also well established that other inhibitors of gastric acid secretion, such as histamine H 2 -receptor antagonists and proton pump inhibitors, reduce oesophageal acidity in subjects with GERD. 8,[36][37][38] When the results from the present study were analysed using conventional methods, such as the number and duration of oesophageal reflux episodes or the percentage of time the oesophageal pH < 4, there was no detectable effect of cisapride on oesophageal acid exposure. On the other hand, using integrated acidity, a more sensitive analytical approach, to assess oesophageal acidity demonstrated a clear statistically significant effect of cisapride.…”
Section: Discussionmentioning
confidence: 58%
“…Indeed, the small cisapride-induced increase in gastric emptying will tend to increase the values calculated for gastric acid secretion, because cisapride will cause the meal to empty more rapidly, reduce the meal buffer capacity in the stomach and, thereby, shorten the titration time (and increase the calculated gastric acid secretion). Although the inhibition of gastric acid secretion is known to decrease the time that the oesophageal pH < 4, 8,[36][37][38] gastric acidity has received limited attention with respect to its potential underlying role in oesophageal acid exposure in GERD. [39][40][41][42][43][44][45] The present finding that cisapride decreases post-prandial oesophageal acid exposure in subjects with GERD agrees with previous findings by others, [11][12][13][14][15] who have attributed this action of cisapride to its motility effects on the lower oesophageal sphincter pressure, oesophageal peristalsis and gastric emptying.…”
Section: Discussionmentioning
confidence: 99%